Southern Photographs 03 : Cuny Janssen - Cera, Michele (s.l. : LAB - Labaratorio di Fotografia di Architettura e Paesaggio, 2013)
Neri, Andrea ; Schiraldi, Vincenzo ; Sgobba, Nicolas ; Caneve, Marina ; Colella, Francesco ; Miraglino, Paolo ; Zanni, Gianni ; Cirillo, Alessandro ; Ranieri, Mariangela ; Cauli, Giodo ; Forte, Costantino et al.
This publication covers a part of the photographic work produced during the 'Southern Photographs 3' workshop held in september 2013 at the archaeological site of Madonna di Grottole, near Polignano a Mare. Fifteen photographers, coming from different areas of Italy, explored the seaside from Polignano a Mare to Cozze. 'Southern Photographs 3' is the third of a series of international photography workshops that the Cultural Association LAB is carrying out of Puglia. (from the cover of the last page)
Publication consists of loose pages
boek
Keywords: Janssen, Cuny